2016
DOI: 10.1080/15569543.2016.1201842
|View full text |Cite
|
Sign up to set email alerts
|

Levels of polychlorinated biphenyls (PCBs) in human adipose tissue from Baghdad/Iraq

Abstract: The levels of 12 polychlorinated biphenyls (PCBs) in human adipose tissue samples gathered from patients, from three different hospitals, in Bagdad/Iraq were analyzed. All samples were extracted, cleaned up, and analyzed by GC/MS for dioxin-like PCBs. The total mean concentration of PCBs in all human adipose tissues samples was 404 mg/kg. Pentachlorobiphenyls were the predominant PCB congeners, accounting for 62.56% of the total PCB concentration found in the human adipose tissue samples which represent the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Polychlorinated biphenyls have been reported in various environmental media ranging from indoor air 8 , 9 , water and sediment 10 , 11 and soil 12 . Of great concern is that these chemicals enter into the food chain where human beings are exposed mainly through the diet and breathing contaminated air, having been detected in human tissue including blood 13 , adipose tissue 14 , liver and kidney 15 . Reported health effects include potential to cause cancer 16 , disruption of the endocrine system, reduced intellectual quotient (IQ) and diabetes 17 among others.…”
Section: Introductionmentioning
confidence: 99%
“…Polychlorinated biphenyls have been reported in various environmental media ranging from indoor air 8 , 9 , water and sediment 10 , 11 and soil 12 . Of great concern is that these chemicals enter into the food chain where human beings are exposed mainly through the diet and breathing contaminated air, having been detected in human tissue including blood 13 , adipose tissue 14 , liver and kidney 15 . Reported health effects include potential to cause cancer 16 , disruption of the endocrine system, reduced intellectual quotient (IQ) and diabetes 17 among others.…”
Section: Introductionmentioning
confidence: 99%
“…Dated sediment core measurements from the northwestern Arabian Gulf identified a 1991 spike in PCBs that may have been due to burning of PCB-containing power transformers during the Iraqi occupation of Kuwait [23]. A study of adipose total PCBs from the Baghdad area of Iraq found levels more than twice the US background, but the source and era of exposure to the PCBs is uncertain [24]. Sulfur mustard, which was detected in fallout from aerial bombing early in the war and which possibly exposed up to 40% of the troops [13], is lipophilic, genotoxic and may be retained in subcutaneous adipose tissue [25].…”
Section: Introductionmentioning
confidence: 99%